PENGGUNAAN TEKNIK MINIMAL PAIRS DRILL DALAM MENINGKATKAN KEMAMPUAN PRONUNCIATION SISWA KELAS 10 SMK PGRI CISAAT SUKABUMI - Aris Muhammad; Usman Diennur; Hasna Hanifah; Intan Dwi Persada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to improve students' pronunciation skills by using the minimal pairs drill technique and to determine students' perceptions after the treatment. This research method is a quasi-experiment. The population of this study were grade X students of SMK PGRI Cisaat Sukabumi consisting of 2 majors and 3 classes. The sampling technique in this study was purposive sampling with a total population of 50 students and the samples of this study were class X TO 1 as the experimental class and X TO 2 as the control class. The experimental class and control class each consisted of 18 students. Data collection was done by giving (pre-test and post-test). This study used t-test as a data analysis technique. The experimental results using this technique showed a higher post-test score compared to the control group, with an average N-Gain of 0.72 or high category compared to 0.14 or low category. The independent t-test results showed a significance level of 0.000 (p,0.05) and a t-value of 7.564, indicating a significant difference between the two. As a result, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted, indicating that the use of the minimal pairs drill technique significantly affected the students' pronunciation improvement. In addition, the results of the questionnaire showed that students gave a very positive response to this technique, showing a boost in their motivation, confidence, and enthusiasm for mastering pronunciation.